Student Management in Supporting the Pancasila Student Profile Strengthening Project at SMPN 5 Banyuasin I - Teguh Sutantri; Bukman Lian; Nuril Furkan (International Journal of Educational Technology and Society, 2025)
This study aims to describe and analyze student management in supporting the Pancasila student profile strengthening project, as well as to the challenges and strategies in overcoming obstacles in implementing student management to support the Pancasila student profile strengthening project. The method used is descriptive qualitative with data collection tools, namely interviews, observations and documentation. Data were analyzed using the interactive model analysis method. The results of the study concluded that student management in supporting the Pancasila student profile strengthening project has implemented the functions and principles of student management through the process of planning, organizing, implementing, and supervising activities carried out properly involving internal elements of the education unit. The challenges in implementing student management in supporting the Pancasila student profile strengthening project include facilities and infrastructure, lack of student motivation, and lack of understanding of the impact of activities on character development. Strategies to overcome the challenges of student management in supporting the Pancasila student profile strengthening project include strengthening teacher competency in managing students, innovative learning, collaboration between schools and parents, stakeholder involvement and participation in school activities, and encouraging student involvement in various activities at school